Effect of Using Different Culture Media on the Growth of Phytoplankton Tetraselmis chuii - Yuniar Nur Maulani; SettingsIda Bagus Jelantik Swasta; Gusti Ngurah Permana; Siyam Sujarwani (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
This study was conducted to determine the effect of different culture media on the growth of Tetraselmis chuii. This study used the experimental method. The treatments used in this study were P1 (GRIM Standard), P2 (GRIM+Clewat-32), P3 (Jasfa Yaeyama), and P4 (GRIM KNO3 Clewat-32). The experimental procedure consisted of a pre-research process to observe and calculate the population density and cell size observation of Tetraselmis chuii. The results showed that different culture media affected the population density of Tetraselmis chuii. Optimum growth was obtained in the culture medium GRIM + KNO3 Clewat-32, reaching 30.3× 106 cells/ml. One-way ANOVA test with a significance level of 95% showed that the difference in media had a significant effect on the growth of Tetraselmis chuii with a value of F = 1.09, P < 0.05. The results of the Duncan test showed that cell density in media A (Grim Standard) was significantly different from media treatments C (Jasfa Yaeyama) and D (GRIM KNO3 Clewat-32). Still, treatment A was not significantly different from treatment B (GRIM Clewat-32), nor was treatment B significantly different from treatments C and D. The cell size of Tetraselmis chuii at the time of the study in all treatments obtained an average value of 6.84 - 11.55 µ. The water quality required for T. chuii is suitable for culture media.